Effectiveness of Remote Glucose Monitoring Versus Conventional Care in Diabetes Management: A Systematic Review and Meta‐Analysis - Peter Olujimi Odutola; Peter Oluwatobi Olorunyomi; Olanrewaju Olamide Olatawura; Ifeoluwapo Olorunyomi (Medicine Advances)
ABSTRACT Diabetes mellitus, especially type 2 diabetes (T2DM), is a growing global health issue characterized by poor blood glucose control, leading to severe complications and increased healthcare costs. Effective management requires accessible, responsive support systems to enhance self‐management, particularly for those with limited access to traditional care. The aim was to evaluate remote monitoring versus standard care in managing diabetes mellitus, focusing on outcomes like Hemoglobin A1C (HbA1C) levels, fasting blood glucose (FBG), lipid profiles, body weight, body mass index (BMI), and blood pressure. A comprehensive literature search was performed in September 2024 using the Cochrane, Google Scholar, and PubMed databases with no time restriction. Seven studies totaling 883 participants were included, comparing remote monitoring with usual care in diabetic management. Data were analyzed using Review Manager (Cochrane), calculating mean differences and 95% confidence intervals (CIs) for continuous data, with statistical significance at p < 0.05. Remote monitoring significantly improved glycemic control, reducing HbA1c levels (mean difference: −0.35; 95% CI: −0.67 to −0.02; p = 0.04) and FBG (mean difference: −0.82; 95% CI: −1.10 to −0.54; p < 0.00001). Total cholesterol levels decreased significantly (mean difference: −0.28; 95% CI: −0.49 to −0.07; p = 0.01). HDL showed a minor but significant decline, while LDL reduction was non‐significant. No significant differences were observed in body weight, BMI, or blood pressure. Remote monitoring shows significant potential in improving glycemic control and lipid profiles in diabetes management. Further long‐term studies are needed to validate these findings, while addressing associated technological challenges.